Orçamento impositivo e emendas parlamentares individuais: uma análise das implicações da adoção da Emenda Constitucional nº 96/2018 pelo estado de Minas Gerais - Castro, Barbara Mendes de (2021)
In Brazil, although most expenses are mandatory, the doctrine characterizes the public budget as merely authoritative, since, with regard to discretionary expenses, there is no guarantee of its realization. The ample actions taken in order to make the public budget more flexible and the political competition in the power relations that surround it, end up frustrating its real role in the Democratic State. This situation was responsible for generating a debate that culminated in recent constitutional changes, at the federal and state levels, related to individual parliamentary amendments. Therefore, this research aims to examine, based on the power relations between Executive and Legislative, the discretionary nature of the budget and its execution perspective, how the individual amendments’s mandatory budget has affected the distribution and implementation of the amendments of this category, in the state of Minas Gerais. To this end, a quantitative analysis of the authorized credit’s distribution and the amendments budget’s execution was carried out among parliamentarians in that state. In order to support the analysis, a wide bibliographic and documentary review of the themes brazilian institutional environment; the role of parliamentary amendments in coalition presidentialism;the dynamics of the public budget in the country - before and after the 1988 Constitution -; the discretionary nature of the annual budget, as well as the mandotory budget’s adoption proposals by the Union and the state of Minas Gerais was made. As a result, it was found that, in general, the mandatory budget was able to reduce the unpredictability of the execution of individual amendments.